Immunosurveillance and immunotherapy of tumors by innate immune cells. (February 2016) - Iannello, Alexandre; Thompson, Thornton W; Ardolino, Michele; Marcus, Assaf; Raulet, David H
Highlights: NK cells and macrophages play a key role in tumor recognition and elimination. NK receptor/ligand interactions underlie tumor recognition and elimination. Expression of ligands for NK receptors in tumor cells is highly regulated. Macrophages eliminate tumors through programmed cell removal and Dectin-1 recognition. The cGAS/STING pathway plays a role in tumor elimination. Abstract : Increasing evidence supports a role for innate immune effector cells in tumor surveillance. Natural killer (NK) cells and myeloid cells represent the two main subsets of innate immune cells possessing efficient but quite different tumor suppressive abilities. Here, we describe the germline-encoded NK cell receptors that play a role in suppressing tumor development and describe briefly the cellular pathways leading to the upregulation of their ligands in tumor cells. We also describe mechanisms underlying the elimination of tumor cells by macrophages and a recently characterized mechanism dedicated to sensing cytosolic DNA that is implicated in antitumor immune responses.